Analisa Pengaruh Pandemic Covid 19 Terkait Kinerja Saham Indeks Lq45 Di Indonesia Periode Februari – April 2020 - Agus Munandar; Nabila Alifa Putri; Setia Utami Amien (Universitas Sains dan Teknologi Komputer, 2022)
This study aims to examine the effect of the Covid 19 pandemic on the performance of LQ45 stocks in Indonesia. The Indonesian Stock Exchange's (IDX) monthly share price of LQ45 is taken into account in this study. Using a quantitative approach, this study compares pre-pandemic and post-pandemic Indonesian COVID 19 epidemic data and hypotheses based on these two sets of data. A causal link comparison study was used to assess the study's validity. According to the results of this study, it can be concluded that the performance of LQ45 shares in Indonesian companies before and after the Covid 19 epidemic was statistically significant. Based on the results of this study, which show that the t-count value is 4.347, with a sig value of 0.000, it is concluded that Ha is accepted and Ho is rejected. During the Covid 19 epidemic, performance of LQ45 share on Indonesia Stock Exchange fell, resulting in the financial losses of several companies.